2012
DOI: 10.1063/1.4740051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrofluoric acid concentration on the evolution of photoluminescence characteristics in porous silicon nanowires prepared by Ag-assisted electroless etching method

Abstract: CitationNajar A, Slimane AB, Hedhili MN, Anjum D, Sougrat R, et al. (2012) We report on the structural and optical properties of porous silicon nanowires (PSiNWs) fabricated using silver (Ag) ions assisted electroless etching method. Silicon nanocrystallites with sizes <5 nm embedded in amorphous silica have been observed from PSiNW samples etched using the optimum hydrofluoric acid (HF) concentration. The strongest photoluminescence (PL) signal has been measured from samples etched with 4.8 M of HF, beyond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…Several mechanisms have been proposed to explain the origin of the remarkable PL emission for SiNWs (indirect gap). These include: (i) the quantum confinement effects, and (ii) SiO x /Si interface defects and/or defect states in the surface of the oxide, related to the Si-O bond [29,30]. Recently, Ghosh et al [26] have revealed that the silicon nanocrystals are responsible for a strong broadband emission of SiNWs, depending on the cross-sectional area of SiNCs.…”
Section: Photoluminescence (Pl) Measurementsmentioning
confidence: 99%
“…Several mechanisms have been proposed to explain the origin of the remarkable PL emission for SiNWs (indirect gap). These include: (i) the quantum confinement effects, and (ii) SiO x /Si interface defects and/or defect states in the surface of the oxide, related to the Si-O bond [29,30]. Recently, Ghosh et al [26] have revealed that the silicon nanocrystals are responsible for a strong broadband emission of SiNWs, depending on the cross-sectional area of SiNCs.…”
Section: Photoluminescence (Pl) Measurementsmentioning
confidence: 99%
“…Therefrom, the opposite trend between the integrated PL intensity and etching duration is plotted in Figure 7. To explain the origin of this PL emission, several mechanisms have been proposed including the quantum confinement (QC) effects and the presence of defects in an SiOx/Si interface and/or in the surface of the oxide related to the Si-O-Si bonds [36,37]. However, the QC effects, which enhance the radiative recombination of excitons, remain the most approved model which dictates that the crystallite Si size should be less than the Bohr radius of the free exciton of bulk silicon [17].…”
Section: Photoluminescence Spectroscopymentioning
confidence: 99%
“…On the other hand, there are numerous studies showing PL from Si nanowires fabricated with two-step etching. 22,28 Figure 1(d) shows the PL spectra of the two-step etched sample. Signal is centered at 697 nm with a fullwidth-half-maximum (FWHM) value of 140 nm, which is consistent with the literature.…”
mentioning
confidence: 99%